Comprehensive Mapping and Dynamics of Site-Specific Prolyl-Hydroxylation, Lysyl-Hydroxylation and Lysyl O-Glycosylation of Collagens Deposited in ECM During Zebrafish Heart Regeneration - Sarohi, Vivek; Srivastava, Shriya; Basak, Trayambak (Frontiers in Molecular Biosciences, 2022)
Cardiac fibrosis is an adaptive response of the myocardium upon any insult/injury. Excessive deposition of collagen molecules in the extracellular matrix (ECM) is the hallmark of fibrosis. This fibrotic response initially protects the myocardium from ventricular rupture. Although in mammals, this fibrotic response progresses towards scar-tissue formation leading to heart-failure(HF); some fishes and urodeles have mastered the art of cardiac regeneration following injury mediated fibrotic response. Zebrafish has unique capability to regenerate the myocardium after post-amputation injury. Following post-amputation, the ECM of zebrafish heart undergoes extensive remodeling and deposits collagen molecules. Collagens being the most abundant protein of ECM plays important role in assembly and cell-matrix interactions. However, the mechanism of ECM remodeling is not well understood. Collagen molecules undergoes heavy post-translational modifications (PTMs) mainly hydroxylation of proline, lysine and glycosylation of lysine during (biosynthesis).The site-specific localization of these collagen PTMs in zebrafish heart ECM is not known. It has remained a daunting challenge to identify the site-specific localization of these collagen PTMs; as these highly modified peptides are not amenable to mass-spectrometry (MS). Here, we have implemented our in-house proteomics analytical pipeline to analyze (PXD011627, PXD010092) ECM proteomics dataset of zebrafish heart during regeneration (post-amputation). We report the first comprehensive site-specific collagen PTM map of zebrafish heart ECM. We have identified a total of 36 collagen chains (19 are newly reported here) harboring a total of 95 prolyl-3-hydroxylation, 108 hydroxylysine, 29 galactosyl-hydroxylysine and 128 glucosylgalactosyl-hydroxylysine sites. Further we comprehensively map the three chains (COL1A1a, COL1A1b, COL1A2) of collagen I, the most abundant protein in zebrafish heart ECM. We achieved more than 95% sequence coverage for all the three chains of collagen I.Our analysis also revealed the dynamics of prolyl-3-hydroxylation occupancy oscillations during heart regeneration at these sites. Moreover, quantitative site-specific analysis of lysyl-glycosylation microheterogeneity during heart regeneration revealed a significant (p<0.05) elevation of site-specific (K1017) glucosylgalactosyl-hydroxylysine on col1a1a chain.Taken together, these site-specific PTM maps and the dynamic changes of site-specific collagen PTMs in ECM during heart regeneration will open up new avenues to decode ECM remodeling and may lay the foundation to tinker cardiac regeneration process with new approaches.